The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11250-007-9020-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a human progesterone enzyme immunoassay (EIA) kit for use on serum of cattle in Cameroon

Abstract: A study aimed at validating a human progesterone enzyme immunoassay kit was carried out on cattle at Bambui, Cameroon. Progesterone ELISA Kits (EH-511) were obtained from Clinpro International. Forty-one cows were selected, of which 19 were pregnant and 22 within 14 days post partum. Blood samples were analysed and progesterone levels were deduced from a curve obtained from standard absorbance values (A450). Results show that 95.5% of postpartum cows had progesterone levels below 1 ng/ ml, with the highest lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…Results showed that both of the ELISA KIT used are capable and have a good validity for measuring both hormones. Other validation tests were also been reported by other researchers to measure progesterone in cattle (Bayemi et al, 2007), and thyroid hormone in donkey (Todini et al, 2010).…”
Section: Biological Validationmentioning
confidence: 87%
See 1 more Smart Citation
“…Results showed that both of the ELISA KIT used are capable and have a good validity for measuring both hormones. Other validation tests were also been reported by other researchers to measure progesterone in cattle (Bayemi et al, 2007), and thyroid hormone in donkey (Todini et al, 2010).…”
Section: Biological Validationmentioning
confidence: 87%
“…The mean percentage of accuracy for this assay was 99.65±4.27% whereas, intra-and inter-assay coefficients of variation (% CV) of high and low value quality controls for the assay precision were below 10% and 15% respectively. Those results indicating that the accuracy and precision of assay were acceptable for measuring serum testosterone in this species (Bayemi et al, 2007;Heisterman, 2010;Bielohuby et al, 2012). Both accuracy and precision reflect how close a measurement is to the actual value.…”
Section: Analytical Validationmentioning
confidence: 91%
“…It is an important reproductive hormone to maintain pregnancy and is produced by the corpus luteum of the ovary. Upon measuring, its blood level concentration increases after ovulation and during pregnancy and reduces during follicular growth after corpus luteum regress and parturition [ 12 ]. Progesterone concentration is maintained by corpus luteum at a high level in pregnant cows compared with non-pregnant cows [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human progesterone ELISA kit was able to make the difference between the PG and NPG cattle; in that, the concentration of progesterone in NPG cows was less than 1.2 ng/ml, while it was above 3 ng/ml for the PG cows. Different experiments for veterinary progesterone kits assert similar distinctions between PG and NPG animals [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cows with 1 ng/ml for two consecutive samples or one sample at or above 3 ng/ml are an indication of the presence of corpus luteum while cows below 1 ng/ml will be in anoestrus. Therefore the kit was used for monitoring post-partum progesterone profiles in dairy herds (Bayemi et al 2007a). Pregnant dairy cows were selected for studies on post partum return to ovarian activity and milk production.…”
Section: Reproductionmentioning
confidence: 99%